2017
DOI: 10.1194/jlr.m076562
|View full text |Cite
|
Sign up to set email alerts
|

The sphingosine 1-phosphate breakdown product, (2E)-hexadecenal, forms protein adducts and glutathione conjugates in vitro

Abstract: Sphingosine 1-phosphate (S1P), a bioactive lipid involved in various physiological processes such as cell proliferation and apoptosis, can be irreversibly cleaved by the S1P lyase, yielding phosphoethanolamine and (2E)-hexadecenal (2EHD). The latter metabolite, an α,β-unsaturated fatty aldehyde, may be susceptible to nucleophilic attack by cellular biomolecules. Hence, we studied whether 2EHD forms reaction products with glutathione (GSH) and proteins in vitro. Using liquid chromatography-tandem mass spectrome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 35 publications
1
18
0
Order By: Relevance
“…Additionally, it can be speculated that an increased expression of S1P lyase is accompanied by an enhanced formation of the cleavage product hexadecenal. As it has been indicated that hexadecenal is a reactive molecule that can form adducts with cellular nucleophiles such as liver proteins, further studies are of interest investigating whether the protein adduct formation of hexadecenal is connected with a dysfunction of hepatic liver proteins [ 19 ].…”
Section: S1p and Hepatocellular Carcinomamentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, it can be speculated that an increased expression of S1P lyase is accompanied by an enhanced formation of the cleavage product hexadecenal. As it has been indicated that hexadecenal is a reactive molecule that can form adducts with cellular nucleophiles such as liver proteins, further studies are of interest investigating whether the protein adduct formation of hexadecenal is connected with a dysfunction of hepatic liver proteins [ 19 ].…”
Section: S1p and Hepatocellular Carcinomamentioning
confidence: 99%
“…The terminal degradation of sphingolipids is initiated by an irreversible cleavage of S1P via S1P lyase, leading to the formation of hexadecenal and phosphoethanolamine. The aldehyde can be further metabolized to palmitoyl CoA, however it has been indicated that hexadecenal is an active compound that can form adducts with cellular nucleophiles such as proteins and glutathione [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, trans-2-hexadecenal reacts readily with deoxyguanosine and DNA to produce the diastereomeric cyclic 1,N(2)-deoxyguanosine adducts 3-(2-deoxy- β -d-erythro-pentofuranosyl)-5,6,7,8-tetrahydro-8R-hydroxy-6R-tridecylpyrimido[1,2-a]purine-10(3H)one and 3-(2-deoxy- β -d-erythro-pentofuranosyl)-5,6,7,8-tetrahydro-8S-hydroxy-6S-tridecylpyrimido[1,2-a]purine-10(3H)one [ 91 ]. Trans-2-hexadecenal forms Michael adduct with glutathione and with seven amino acids [ 92 ]. It also binds directly to Bax, leading to a conformational change in Bax, resulting in its activation, which induces apoptosis ( Figure 1(b) ) [ 24 , 25 ].…”
Section: Structure and Functions Of Splmentioning
confidence: 99%
“…2 Little is known about the biological role of 2HD. 4,5 We were the first to discover a new nonenzymatic pathway of 2HD formation from sphingolipids under the action of gamma radiation and UV light. 3 It has been reported that 2HD forms adducts with DNA and conjugates with glutathione.…”
mentioning
confidence: 99%
“…3 It has been reported that 2HD forms adducts with DNA and conjugates with glutathione. 4,5 We were the first to discover a new nonenzymatic pathway of 2HD formation from sphingolipids under the action of gamma radiation and UV light. We have established that when reactive oxygen All authors contributed equally to this work.…”
mentioning
confidence: 99%